2008
DOI: 10.1017/s0265021507002608
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by isoflurane vs. sevoflurane in ultra-fast-track anaesthesia for off-pump aortocoronary bypass grafting

Abstract: This study indicates that during off-pump cardiac bypass surgery, sevoflurane and isoflurane provide the same ischaemic cardioprotective effects. There is no difference for heart contractility and haemodynamic values during and after off-pump cardiac bypass surgery between the two agents. Sevoflurane allows a more rapid recovery from anaesthesia, but this does not translate into better pulmonary function or haemodynamics. Both agents are similar in ultra-fast-track off-pump cardiac bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…22 Sevoflurane was found to be cardioprotective in patients undergoing cardiac surgery. [10][11][12][13] In the current study, we did not find a difference in the degree of myocardial injury between the sevoflurane and the control groups. Patients in both groups received pPCI relatively quickly, along with contemporary medical therapy that included, in most patients, administration of IIbIIIa inhibitors and frequent use of aspiration thrombectomy.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…22 Sevoflurane was found to be cardioprotective in patients undergoing cardiac surgery. [10][11][12][13] In the current study, we did not find a difference in the degree of myocardial injury between the sevoflurane and the control groups. Patients in both groups received pPCI relatively quickly, along with contemporary medical therapy that included, in most patients, administration of IIbIIIa inhibitors and frequent use of aspiration thrombectomy.…”
Section: Discussioncontrasting
confidence: 61%
“…Sevoflurane administration during cardiac surgery was found to reduce the incidence of MI, intensive care unit and hospital stay, time on mechanical ventilation, in-hospital mortality, and long-term cardiac events. [10][11][12][13] A recent meta-analysis demonstrated that volatile agents and, in particular, sevoflurane and desflurane reduce mortality after cardiac surgery compared with intravenous anesthesia. 14 There are few data regarding the effect of sevoflurane during PCI.…”
mentioning
confidence: 99%
“…We avoided the use of desflurane because of tachycardia [11]. Isoflurane and sevoflurane have been shown to be quite similar in outcome [12]. The direct cardiac effects of Thiopentone and Propofol do not show significant differences when compared in vivo [13].…”
Section: Discussionmentioning
confidence: 99%
“…9 When compared with intravenous anesthesia, sevoflurane has been shown to reduce the incidence of MI and intensive care unit stay, the length of time on mechanical ventilation following cardiac surgery, in-hospital mortality, and long-term cardiac events. [10][11][12][13][14] The effect of sevoflurane as a cardioprotective agent has not been shown in all studies, 15 and results were also dependent on duration of administration, number of exposures, and dose. For instance, in one study, the beneficial effects were observed only when administered throughout the surgery and not when administered in a fashion similar to ischemic conditioning, before cardiopulmonary bypass, or following the creation of the coronary anastomosis.…”
Section: Résumémentioning
confidence: 91%